Microtensile Bond Strength of Different Components of Core Veneered All-Ceramic Restorations. Part 3: Double Veneer Technique - Moustafa N. Aboushelib, DDS, MSc,1,2 Cornelis J. Kleverlaan, PhD,1 & Albert J. Feilzer, PhD, DDS1 (Journal of Prosthodontics, 2008)
The bond strength of zirconia veneer has been considered a weak link in the layered all-ceramic restoration.